A detailed calculation model for costing of green manufacturing. Issue 1 (1st February 2016) - Orji, Ifeyinwa; Wei, Sun
Abstract : Purpose: – Manufacturing firms are expected to implement green manufacturing and increase product complexity at a competitive price. However, a major problem for engineering managers is to ascertain the costs of embarking on green manufacturing. Thus, a planning and control methodology for costing of green manufacturing at the early design stage is important for engineering managers. The paper aims to discuss these issues. Design/methodology/approach: – This paper integrates "green manufacturing, " concepts of industrial dynamics, and product lifecycle aiming at developing a methodology for cost calculation. The methodology comprises of a process-based cost model and a systems dynamics (SD) model. The process-based cost model focusses mainly on carbon emission costs and energy-saving activities. Important metrics usually ignored in traditional static modeling were incorporated using SD model. Findings: – Equipment costs and carbon emission costs are major components of costs in manufacturing. The total life cycle cost of product in green manufacturing is lower than that of same product in conventional manufacturing. Research limitations/implications: – The specific results of this study are limited to the case company, but can hopefully contribute to further research on ascertaining cost of implementing "green issues" in manufacturing. The proposed cost calculation model can be efficiently applied in any manufacturing firm on the basis of accessibility of real cost data. This necessitates a comprehensive cost database. At the development of the model and database management system, time and cost resources could be demanding, but once installed, use of the model becomes less demanding. Practical implications: – The cost model provides cost justifications of implementing green manufacturing. The reality is that green manufacturing will see its development peak with cost justifications. The results of the application show that the proposed detailed cost model can be effective in ascertaining costs of implementing green manufacturing. Manufacturing firms are recommended to adopt energy-saving activities based on the proposed detailed cost calculation model. Originality/value: – The main contributions of the study includes: first, to help engineering managers more accurately understand how to allocate resources for energy-saving activities through appropriate cost drivers. Second, to simulate with SD the dynamic behavior of few important metrics, often ignored in traditional mathematical modeling. The detailed model provides a pre-manufacturing decision-making tool which will assist management in implementing green manufacturing by incorporating a life cycle assessment measurement into manufacturing cost management.